La propiedad comunitaria indígena - Abreut de Bregher, Liliana (2012)
The recognition of aboriginal rights and its legal treatment in Argentina\nwent through a big change in the early 20th century. This article explains this change\nand compares the regulation in the 19th century with its regulation nowadays.\nFrom a historical perspective, the author analyzes the different periods of Argentinian\nhistory, its changes in mentality and their effects in constitutional law. Describing the\nwritten constitutions of the 19th century, emphasis is given to the monocultural model,\nwhich changed with the Constitution of 1994 into a multicultural model. Furthermore, it is questioned if the treatment of the aboriginal property corresponds to\nprivate law, and the distinct characteristics of this new ?rights in rem? will be analyzed